Udział środowiskowych wspólnot komunikatywnych w kształtowaniu słownictwa ogólnopolskiego (rzecz o "damie" i "facecie") = Of Ladies and Guys: the Role of local communicative communities in Shaping general polish Vocabulary - Siatkowska, Ewa (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
"Communication community" is a notion coined by German researchers and transplanted into Polish by Leon Zabrodzki, then specified and developed by Stanisław Borawski. The article discusses the role of communication communities in popularization of the words "dama" and "facet", originally used in jargon, in the vernacular used nationwide.
Keywords: wspólnota komunikatywna; język ogólnonarodowy; język środowiskowy; communication community; vernacular; jargon